Effects of dietary supplementation with Bacillus subtilis and bacteriophage on growth performance, intestinal morphology and microbiota structure in 0–90 d MaGang geese - Chenyu Zhu; Yongquan Luo; Kunjie Xu; Yong Li; Yuanhao Han; Zhiyuan Liu; Xiujin Li; Danning Xu; Yunbo Tian; Yunmao Huang; Zhongping Wu; Xumeng Zhang (Frontiers in Nutrition)
IntroductionThe expansion of large-scale goose farming under semi-arid conditions has exacerbated bathing pool pollution, adversely affecting goose growth performance and intestinal health. Given the crucial role of gut microbiota in maintaining intestinal homeostasis, and considering the reported beneficial effects of bacteriophages and Bacillus subtilis on gut health, this study investigated their combined application in goose production.MethodsTo investigate the effects of Bacillus subtilis and phage supplementation on goose intestinal health, a 90-day trial was conducted with 288 Magang goslings randomly allocated to four treatment groups: control (A), B. subtilis (1 × 105 CFU/kg; B), bacteriophage (5 × 107 PFU/kg; C), and combined supplementation (D).ResultsThe supplementation significantly enhanced body weight (p < 0.05) and feed efficiency without affecting feed intake. Notably, the combined treatment demonstrated synergistic effects in reducing serum and aquatic endotoxin levels while suppressing pathogenic bacteria (Escherichia coli and Salmonella) in water systems. Intestinal morphology improvements included increased villus height and optimized villusto-crypt ratios, accompanied by up-regulated expression of tight junction genes (Zo-1 and Ocln). Cecal microbiota analysis revealed enhanced alpha diversity and a shift toward Bacteroides-dominant communities, with concurrent suppression of Proteobacteria. Immune modulation exhibited a biphasic response, characterized by early anti-inflammatory (Tnf-α) and late-phase antioxidant (Ho-1) activities. Microbialenvironmental correlation analysis identified Firmicutes and Desulfobacterota as growth-promoting but barrier-compromising taxa, while Bacteroidota was associated with improved gut integrity.ConclusionThis research has shown that adding B. subtilis and bacteriophages to feed significantly enhances the intestinal barrier function of geese. The findings demonstrate that combined supplementation of B. subtilis and bacteriophages during the brooding and rearing stages optimizes growth performance through gut-microbiota-immune interactions, providing an effective antibiotic-free strategy for sustainable poultry production.